Regional control is preserved after dose de-escalated radiotherapy to involved lymph nodes in HPV positive oropharyngeal cancer. (February 2016) - Woody, Neil M.; Koyfman, Shlomo A.; Xia, Ping; Yu, Naichang; Shang, Qingyang; Adelstein, David J.; Scharpf, Joseph; Burkey, Brian; Nwizu, Tobenna; Saxton, Jerold; Greskovich, John F.
Highlights: We review HPV+ oropharyngeal cancer treated with lower radiation dose to involved lymph nodes. Full dose radiation (>70 Gy) was given to primary tumors with concurrent chemotherapy. Adjuvant lymph node dissection was omitted in all cases due to complete response. 5 year locoregional control and overall survival were 96% and 86% respectively. Lower radiotherapy dose to involved nodes did not compromise regional control. Summary: Objectives: To analyze a cohort of patients with HPV positive, oropharyngeal squamous cell carcinoma (OPSCC) treated with lower radiation dose to clinically involved lymph nodes. Materials and methods: We retrospectively identified patients with HPV positive, OPSCC treated with definitive chemoradiotherapy (70–74.4 Gy) to the primary site and, since a post-radiation neck dissection was planned, 54 Gy to the involved nodal areas. Neck dissection was ultimately omitted in all cases due to complete response. All patients were treated with a 3 field approach with sequential boost plans. Composite plans were generated retrospectively and primary tumor and lymph node GTVs were contoured and nodes were expanded by 5 mm to form a CTV. Mean dose, dose to 95% (D95) and dose to 99% (D99) were determined. Results: Fifty patients treated from 2008 to 2010 with 113 involved nodes were identified. The median age was 57 years, and 6%, 46%, and 48% were current, former, and never smokers. Ninety percent of patients received concurrent cisplatin based chemotherapy. Median D95 and D99 to involved nodes were 59.8 Gy and 55.9 Gy respectively. At a median follow up of 54.1 months, two patients developed nodal failure and four developed metastatic disease. Five year loco-regional control, disease free survival and overall survival were 96%, 81% and 86% respectively. Conclusion: In this exploratory analysis, regional lymph node control in HPV positive oropharyngeal cancer was not compromised by dose de-escalated radiotherapy to involved nodes in the setting of concurrent cisplatin based chemotherapy.